Characteristics of Foot‐and‐Mouth Disease Viral Strains Circulating at the Wildlife/livestock Interface of the Great Limpopo Transfrontier Conservation Area. Issue 1 (17th April 2014) - Jori, F.; Caron, A.; Thompson, P. N.; Dwarka, R.; Foggin, C.; de Garine‐Wichatitsky, M.; Hofmeyr, M.; Van Heerden, J.; Heath, L.
Summary: Foot‐and‐mouth disease (FMD) inflicts severe economic losses within infected countries and is arguably the most important trade‐restricting livestock disease in the world. In southern Africa, infected African buffaloes ( Syncerus caffer ) are the major reservoir of the South African Territories (SAT) types of the virus. With the progressive expansion of transfrontier conservation areas (TFCAs), the risk of FMD outbreaks is expected to increase due to a higher probability of buffalo/livestock contacts. To investigate the dynamics of FMD within and around the Great Limpopo TFCA (GLTFCA), 5 herds of buffaloes were sampled in June 2010 to characterize circulating viruses in South Africa and Zimbabwe. Three SAT‐2 and three SAT‐3 viral strains were isolated in both countries, including one that was genetically linked with a recent SAT‐2 outbreak in Mozambique in 2011. In addition, two groups of unvaccinated cattle ( n = 192) were serologically monitored for 1 year at the wildlife/livestock interface of Gonarezhou National Park (GNP) in Zimbabwe between April 2009 and January 2010, using the liquid‐phase blocking ELISA (LPBE) and a test for antibodies directed against non‐structural proteins (NSP). Neither clinical signs nor vaccination of cattle were reported during the study, yet a high proportion of the monitored cattle showed antibody responses against SAT‐3 and SAT‐1. Antibodies against NSP were also detected in 10% of the monitored cattle. The results of this study suggest that cattle grazing in areas adjacent to the GLTFCA can be infected by buffalo or other infected livestock and that cattle trade movements can act as efficient disseminators of FMD viruses to areas several hundred kilometres from the virus source. Current methods of surveillance of FMD at the GLTFCA interface seem insufficient to control for FMD emergence and dissemination and require urgent reassessment and regional coordination.